PENAMBAHAN LAPANGAN BOLA VOLI UNTUK MENDUKUNG MINAT SERTA MENINGKATKAN INFRASTRUKTUR DESA DARMA - Febianti, Yopi Nisa; Ar-Rasyid, Rafif Harun; Angelica, Angelica; Nabilah, Fityah; Shevaulia, Hana Sri; Aaliyah, Syahlaa; Mulyawati, Yusriyani; Zahra, Firda Annisa; Fauziyyah, Hany; ‘Aini, Shofi Qurrotul; Putra, Reihan Tridamar; Sari, Atik Yuliana; Arbiansyah, Muhammad Nabil; Nuriyanti, Nuriyanti; Bakti, Ridwan; Aini, Anis Nuru (STKIP Persada Khatulistiwa Sintang, 2025)
ABSTRACTProvision of adequate sports facilities is an important factor in increasing community participation in physical activities. Darma Village has great potential in the field of sports, especially volleyball, but the lack of volleyball courts is an obstacle for residents. Therefore, Thematic KKN students took the initiative to build a volleyball court as a form of utilizing available empty land. The method used in this activity is the Asset-Based Community Development (ABCD) approach, which involves the stages of inculturation, discovery, design, definition, and reflection. The results of the activity showed an increase in community interest in sports and the formation of cooperation between students and residents in village infrastructure development. In addition, the existence of the field is also a means to strengthen social relations between residents. With this facility, it is hoped that the community will be more active in exercising, thereby improving their quality of life and health.Keywords: Volleyball Court, Sports Facilities, Interest, Village Infrastructure, Thematic KKN.ABSTRAKPengadaan fasilitas olahraga yang memadai merupakan faktor penting dalam meningkatkan partisipasi masyarakat dalam aktivitas fisik. Desa Darma memiliki potensi besar dalam bidang olahraga, khususnya bola voli, namun kurangnya lapangan voli menjadi kendala bagi warga. Oleh karena itu, mahasiswa KKN Tematik berinisiatif untuk membangun lapangan voli sebagai bentuk pemanfaatan lahan kosong yang tersedia. Metode yang digunakan dalam kegiatan ini adalah pendekatan Asset-Based Community Development (ABCD), yang melibatkan tahap inkulturasi, discovery, design, define, dan reflection. Hasil kegiatan menunjukkan adanya peningkatan minat masyarakat terhadap olahraga voli serta terbentuknya kerja sama antara mahasiswa dan warga dalam pembangunan infrastruktur desa. Selain itu, keberadaan lapangan voli juga menjadi sarana untuk mempererat hubungan sosial antarwarga. Dengan adanya fasilitas ini, diharapkan masyarakat lebih aktif dalam berolahraga, sehingga meningkatkan kualitas hidup dan kesehatan mereka.Kata kunci: Lapangan Voli, Sarana Olahraga, Minat, Infrastruktur Desa, KKN Tematik.